Energy Law and Regulation in Brazil (Springer International Publishing, 2018)
The book presents contributions from Brazilian experts on the regulation of different energy sources. Focusing on describing and discussing the fundamental issues related to the legal regulation of each of the sources that compose Brazil's energy matrix, it also analyzes economic and strategic aspects and identifies the main current problems related to the exploration for and production of each energy source. The book offers a clear and detailed overview of energy law and regulation for policymakers, foreign investors and legal professionals dealing with energy projects in Brazil.